2015
DOI: 10.1515/humor-2015-0095
|View full text |Cite
|
Sign up to set email alerts
|

An examination of the convergence between the conceptualization and the measurement of humor styles: A study of the construct validity of the Humor Styles Questionnaire

Abstract: The Humor Styles Questionnaire (HSQ; Martin et al. 2003) was devel-oped using a constructbased scale construction approach to measure four humor styles, namely affiliative, self-enhancing, aggressive, and self-defeating. The present study investigates to what extent the HSQ scales converge with and represent the conceptualizations (i.e., the definitions and construct descrip-tions) of the four humor styles as outlined by Martin et al. (2003). To this end, 340 participants provided self-reports on the definitio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
12
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
3

Relationship

2
8

Authors

Journals

citations
Cited by 33 publications
(16 citation statements)
references
References 20 publications
4
12
0
Order By: Relevance
“…Mediating effects were not found for Affiliative and Aggressive humor. Furthermore, these findings add to the already extensive literature that supports the discriminant and construct validity of the four scales of the HSQ ( Martin, 2015 ; see Heintz & Ruch, 2015 ). From a treatment perspective, increasing use of adaptive coping strategies for managing stressful situations (in particular use of Self-Enhancing humor) and decreasing use of maladaptive strategies may be useful for individuals experiencing depressive symptoms.…”
Section: Discussionsupporting
confidence: 69%
“…Mediating effects were not found for Affiliative and Aggressive humor. Furthermore, these findings add to the already extensive literature that supports the discriminant and construct validity of the four scales of the HSQ ( Martin, 2015 ; see Heintz & Ruch, 2015 ). From a treatment perspective, increasing use of adaptive coping strategies for managing stressful situations (in particular use of Self-Enhancing humor) and decreasing use of maladaptive strategies may be useful for individuals experiencing depressive symptoms.…”
Section: Discussionsupporting
confidence: 69%
“…Furthermore, it has been also suggested that the humour present in laughing at oneself could be associated with prosocial behaviours that are characteristic of agreeableness and extroversion . Therefore, further research is needed: first, to determine whether these discrepancies are explained by contextual factors (cultural or work‐based differences), and second, to continue exploring the construct/criterion validity of the self‐defeating humour dimension .…”
Section: Discussionmentioning
confidence: 99%
“…Although it has been shown that the study of the relationship between humor and (facets of subjective) well-being has several pitfalls (Heintz & Ruch, 2015;Ruch & Heintz, 2014), humor seems to have a potential to contribute to people's well-being. For example, correlational studies using (self-and peer-ratings of) character strengths consistently show robust positive relations in the upper range of the VIA strengths (e.g., Park, Peterson, & Seligman, 2004;Proyer, Ruch, and Buschor, 2013;Proyer, Gander, Wellenzohn, & Ruch, 2013).…”
Section: Introductionmentioning
confidence: 99%